키르케고아에서 불안의 의미 -도덕교육과 관련하여 - 황종환; Jong Hwan Hwang (윤리연구, 1(71), 2008)
인간은 불안에서 벗어나고자 하지만 불안하기 때문에 오히려 자신을 찾아 나설 수 있다. 이 논문은 키르케고아의 『불안의 개념』을 중심으로 인간실존을 이해하면서 현재 도덕발달 중심의 도덕교육의 한계를 극복해보고자 한다. 키르케고아가 추구한 바는 도덕교육의 정체(正體)성으로서 자아를 형성하는 것이고, 다른 사람도 이런 삶을 살도록 간접전달(indirect communication)의 방법 즉 말이나 지시를 통한 직접적 교훈이 아니라 전달자가 실제로 전달하고자 하는 내용의 삶을 실제적으로 살고자 하였다. 키르케고아는 인간정신이 신과 영원한 관계를 맺는 방법으로 우선 자기 자신과 관계하고 나아가 타인과 관계하며 이 관계는 오늘날의 지평에서 보면 자연에까지 확장되게 된다. 그에게 인간이 타자와 관계하는 이분법적 사유방식은 자아와 타자의 관계로서 환원될 수 없고 오직 신과 관계에서만 해결될 수 있다. 그에게 사람은 신과 단독자적 실존의 관계에서 자기 자신이 되는 과정을 통하여 자신을 알아가게 되며 이는 자기화로서 도덕교육으로 이해된다. 즉 자기를 앎이 곧 전체를 앎이다(unum noris omnes). This study tries to understand human being in the state of anxiety to find new insights into moral education. Anxiety in S. Kierkegaard has ambivalent meaning. Anxiety is in Psychology and Psychoanalysis negative symptom, which should be cured. In 『The Concept of Anxiety』Kierkegaard maintains that anxiety is the key for human being to appropriating oneself by existential transcending before God. Human being in Kierkegaard should pursue his moral identity by qualitative leaping before God, This relation is the presupposition for the relation between man and himself, others, and nature. Essential meaning of humanness in Kierkegaard. cannot be gained by scientific study. The qualitative leap is concreted not by scientific observation, but by spiritual experience. R. Manheimer tries to understand Kierkegaard in the perspective of moral education. For Manheimer the essence and end of moral education is the process to find out oneself, namely appropriation. Kierkegaard tries to communicate moral development by indirect way, which means not by just theoretical teaching but by concrete existential life. For Kierkegaard to know oneself means to know all(unum noris omnes). KCI Citation Count: 1